Understanding the role of mobile ad hoc networks in non-traditional contexts - Aldunate, Roberto G. (2006)
With the rapid development of short-range wireless technology new venues to apply it in more sophisticated, complex, and dynamic environments have been opened. Nevertheless, the applicability of such technology in nontraditional settings like face-to-face encounters and disaster relief environments, remains unclear. This article describes a research effort aimed to narrow that gap by means of using two non-traditional settings as case studies; face-to-face encounters among unacquainted people and first responders in urban disaster relief environments. Among the results obtained are: a) interactions among unacquainted people may be promoted, though the level of interaction becomes easily constrained due to the current state of RF technology and the design of the experiments, and b) it is feasible to obtain a reliable communication platform for first responders operating in disaster relief missions. These results supports the idea that short-range wireless technology may play both a facilitator and a promoter role in face-to-face contexts, and at least a facilitator role in the case of users co-located in highly dynamic contexts.